2014
DOI: 10.1186/1750-1172-9-95
|View full text |Cite
|
Sign up to set email alerts
|

Modeling changes in biomarkers in Gaucher disease patients receiving enzyme replacement therapy using a pathophysiological model

Abstract: BackgroundGaucher disease (GD) is a rare recessively inherited disorder caused by deficiency of a lysosomal enzyme, glucocerebrosidase. Accumulation of glucosylceramide or glucosylsphingosine in macrophages leads to increased production of ferritin and chitotriosidase and to decreases in hemoglobin concentration and platelet count, which are used as blood biomarkers. GD is treated by enzyme replacement therapy (ERT) or, sometimes by substrate reduction therapy. However, no physiological model for analysis of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The observed serial changes in DS3 scores and transitions in GD1 health states (mild, moderate, marked) further demonstrate not only the short-term and longer-term effectiveness of ERT for reversing and controlling common GD1 manifestations but also reveal some of its limitations. In that significant improvement in DS3 scores is largely confined to the first 5 years from inception of treatment followed by a 5-20 year plateau, our findings mirror earlier reports that are more narrowly concentrated than the composite DS3 score on hematological and visceral responses or on changes in surrogate biomarkers such as serum ferritin and chitotriosidase [ 34 – 37 ]. However, the DS3 methodology may be insufficiently sensitive to reflect changes in manifestations that respond relatively slowly to ERT such as bone mineral density [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…The observed serial changes in DS3 scores and transitions in GD1 health states (mild, moderate, marked) further demonstrate not only the short-term and longer-term effectiveness of ERT for reversing and controlling common GD1 manifestations but also reveal some of its limitations. In that significant improvement in DS3 scores is largely confined to the first 5 years from inception of treatment followed by a 5-20 year plateau, our findings mirror earlier reports that are more narrowly concentrated than the composite DS3 score on hematological and visceral responses or on changes in surrogate biomarkers such as serum ferritin and chitotriosidase [ 34 – 37 ]. However, the DS3 methodology may be insufficiently sensitive to reflect changes in manifestations that respond relatively slowly to ERT such as bone mineral density [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…As expected, the response to ERT decreased the sizes of the spleen and the liver and increased Hb and Hematocrit (Hct) values as well as platelet counts. 5 GD ERT patients also exhibited lower chitotriosidase activity and CC chemokine ligand 18 (CCL18) levels as compared with GD UT patients. Surprisingly, ERT neither reduced the RBC adhesiveness to laminin nor the expression of Lu/BCAM (see Table 1).…”
Section: Effect Of Velaglucerase Alfa Enzyme Replacement Therapy On Rmentioning
confidence: 99%
“…We analyzed the relationship between hospital teaching status and clinical outcomes among adult patients with a primary discharge diagnosis of AML using the National Inpatient Sample (NIS) from 2008 to 2013. The NIS is part of the Healthcare Cost and Utilization Project (HCUP) that is sponsored by the Agency for Healthcare Research and Quality 5. Each year of the NIS includes over seven million inpatient stays from U.S. hospitals and represents more than 95% of the U.S. On unadjusted analyses, patients at non-teaching hospitals were older (mean age 67.1 years vs. 58.1 years, P < .0001) and had a higher Charlson comorbidity index (CCI) (mean 3.05 vs. 2.78, P < .0001).…”
mentioning
confidence: 99%
“…The first study to report hyperferritinemia over the course of GD was published by Morgan et al (1983) , and since then these findings have been replicated in different cohorts worldwide ( Poll et al , 2002 ; Grosbois et al , 2009 ; Saadi et al , 2010 ; Stein et al , 2010 ; Stirnemann et al , 2010 ; Stirnemann et al , 2011 ; Mekinian et al , 2012 ). The reduction in SF exhibited by patients with GD undergoing ERT could be indicative of a positive clinical outcome ( Stirnemann et al , 2010 ; Vigan et al , 2014 ), although no studies to date have identified a clear association between SF levels and GD severity. In Brazilian patients, these findings have yet to be replicated.…”
Section: Introductionmentioning
confidence: 99%